The gene Sr38 for bread wheat breeding in Western Siberia - E. S. Skolotneva; V. N. Kelbin; V. P. Shamanin; N. I. Boyko; V. A. Aparina; E. A. Salina (Вавиловский журнал генетики и селекции)
Present-day wheat breeding for immunity exploits extensively closely related species from the family Triticeae as gene donors. The 2NS/2AS translocation has been introduced into the genome of the cultivated cereal Triticum aestivum from the wild relative T. ventricosum. It contains the Lr37, Yr17, and Sr38 genes, which support seedling resistance to the pathogens Puccinia triticina Eriks., P. striiformis West. f. sp. tritici, and P. graminis Pers. f. sp. tritici Eriks. & E. Henn, which cause brown, yellow, and stem rust of wheat, respectively. This translocation is present in the varieties Trident, Madsen, and Rendezvous grown worldwide and in the Russian varieties Morozko, Svarog, Graf, Marquis, and Homer bred in southern regions. However, the Sr38 gene has not yet been introduced into commercial varieties in West Siberia; thus, it remains of practical importance for breeding in areas where populations of P. graminis f. sp. tritici are represented by avirulent clones. The main goal of this work was to analyze the frequency of clones (a)virulent to the Sr38 gene in an extended West Siberian collection of stem rust agent isolates. In 2019–2020, 139 single pustule isolates of P. graminis f. sp. tritici were obtained on seedlings of the standard susceptible cultivar Khakasskaya in an environmentally controlled laboratory (Institute of Cytology and Genetics SB RAS) from samples of urediniospores collected on commercial and experimental bread wheat fields in the Novosibirsk, Omsk, Altai, and Krasnoyarsk regions. By inoculating test wheat genotypes carrying Sr38 (VPM1 and Trident), variations in the purity of (a)virulent clones were detected in geographical samples of P. graminis f. sp. tritici. In general, clones avirulent to Sr38 constitute 60 % of the West Siberian fungus population, whereas not a single virulent isolate was detected in the Krasnoyarsk collection. The Russian breeding material was screened for sources of the stem rust resistance gene by using molecular markers specific to the 2NS/2AS translocation. A collection of hybrid lines and varieties of bread spring wheat adapted to West Siberia (Omsk SAU) was analyzed to identify accessions promising for the region. The presence of the gene was postulated by genotyping with specific primers (VENTRIUP-LN2) and phytopathological tests with avirulent clones of the fungus. Dominant Sr38 alleles were identified in Lutescens 12-18, Lutescens 81-17, Lutescens 66-16, Erythrospermum 79/07, 9-31, and 8-26. On the grounds of the composition of the West Siberian P. graminis f. sp. tritici population, the Sr38 gene can be considered a candidate for pyramiding genotypes promising for the Novosibirsk, Altai, and Krasnoyarsk regions.